2016
DOI: 10.1007/s10900-016-0228-0
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccine Uptake in Texas Pediatric Care Settings: A Statewide Survey of Healthcare Professionals

Abstract: The purpose of this study was to identify barriers to and facilitators of human papillomavirus (HPV) vaccination in children aged 9–17 years across Texas. A literature review informed the development of a web-based survey designed for people whose work involves HPV vaccination in settings serving pediatric patients. The survey was used to examine current HPV vaccine recommendation practices among healthcare providers, barriers to HPV vaccination, reasons for parent/caregiver vaccine refusal, staff and family e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 4 publications
0
28
2
Order By: Relevance
“…Although the survey of Texas healthcare practitioners reports HPV vaccination recommendations at 94%, 34 this percentage is much lower in this study. There was a nearly even split on whether healthcare providers had recommended or not recommended the HPV vaccine to the study sample.…”
Section: Future Efforts To Improve Hpv Vaccine Uptakecontrasting
confidence: 63%
See 1 more Smart Citation
“…Although the survey of Texas healthcare practitioners reports HPV vaccination recommendations at 94%, 34 this percentage is much lower in this study. There was a nearly even split on whether healthcare providers had recommended or not recommended the HPV vaccine to the study sample.…”
Section: Future Efforts To Improve Hpv Vaccine Uptakecontrasting
confidence: 63%
“…[31][32][33] A recent survey of Texas healthcare providers found that 94% self-reported giving a consistent recommendation of HPV vaccination to 9-12-year-old children of both sexes. 34 Factors associated with vaccine uptake Factors shown to be positively associated with parents' uptake of HPV vaccines for their children include: (1) healthcare providerphysician recommendation and parents' trust in healthcare providers, 20,21,25,26,33 (2) mother as HPV vaccine decision-maker versus both parents, 20 (3) parents' vaccine beliefs, attitudes, and intentions, 20,35 (4) preventive healthcare utilization for child, 28 (5) insurance / costhealth insurance coverage of HPV vaccination, 28 (6) parents' HPV risk history, 20 7parents' HPV-related knowledge and awareness, 28 and (8) sociodemographic factorsurban versus rural location and child's age. 20,21,25,26,33 For those who have chosen to not vaccinate against HPV, parents cite lack of knowledge and worry about the side effects or safety of the vaccine as the primary reasons for vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
“…(Leib et al, 2011). Javaid et al (2017) conducted a study on the barriers to the Gardasil vaccine. The researchers sent surveys via email to medical facilities in the state of…”
Section: Medical Provider Views On Vaccinementioning
confidence: 99%
“…A descriptive statistics analysis was conducted using the survey software, Qualtrics. Javaid et al (2017) found that parental perceptions about HPV, parental knowledge, and safety concerns were barriers affecting Gardasil vaccine rates (Javaid et al, 2017).…”
Section: Medical Provider Views On Vaccinementioning
confidence: 99%
See 1 more Smart Citation